Surgical management of extramedullary plasmacytoma (EMP) in the ear canal of a dog - Lavanya, T. R.; Selvarajah, G. T.; Radzi, R.; Kok, M. K.; Ong, S. M. (Malaysian Veterinary Medical Association, 2024)
Extramedullary plasmacytomas (EMPs) have been commonly reported to occur at solitary sites involving the skin of the digits, lips, and ears. An 8-year-old castrated local dog was presented for a mass obstructing the right ear canal. On physical examination, an ulcerated, pink, firm mass at the base of the pinna with active bleeding was observed. Radiography and computed tomography revealed stenosis of the right horizontal ear canal and soft tissue attenuation of the external auditory canal with thickening of the tympanic membrane respectively. Total ear canal ablation with lateral bulla osteotomy was performed. Histopathological examination confirmed the mass to be a plasmacytoma. The dog had an uneventful recovery.